From teacher methods to school sustainability: A systematic literature review - Yihong Peng; Bity Salwana Alias; Azlin Norhaini Mansor (Environment and Social Psychology, 2025)
The effects of teaching strategies on school sustainability over a ten-year period are examined in this systematic literature review (SLR). Using the PRISMA technique, the study thoroughly analysed six databases and identified 80 papers that need further investigation. Content analysis was refined iteratively, starting with automatic analysis using Leximancer. The researcher's point of view influenced the analysis's final development. The study underlined the wide range of applications and enduring effects of teaching practices on school sustainability, underscoring their vital role in improving academic standards and ensuring the adaptability and durability of educational institutions. In order to shape successful educational practices, direct professional development, and inform policy frameworks that promote long-term institutional resilience, this SLR tackles significant gaps in the literature and presents numerous important improvements. Adopting multidisciplinary, emotionally intelligent, culturally sensitive, and technologically advanced techniques is also essential to the future of sustainability in teaching ethics. Future studies can support more inclusive, transformative, and successful sustainability teaching methods in a variety of educational contexts by tackling these new areas.